Kepastian Hukum Klaim Polis Asuransi Jiwa terkait Wanprestasi Perusahaan Asuransi dalam Pembayaran Klaim - Adam Ramadani; Iran Sahril; Felicitas Sri Marniati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Discussion on the legal certainty of life insurance policy claims related to insurance company default in paying claims. The method used in this study is a normative juridical research type, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The results of the study on the regulation and legal consequences of insurance policies related to default are that the emergence of life insurance beneficiaries results in creating a legal relationship between life insurance beneficiaries, the existence of insurance company default, so that the beneficiaries can obtain their rights. The legal certainty of life insurance policies related to insurance company default in paying claims to life insurance beneficiaries is that life insurance policies made based on the agreement of the parties and fulfilling the legal requirements of the agreement as stipulated in Article 1320 of the Civil Code have binding force as a law for the parties (pacta sunt servanda), and Article 31 of Law of the Republic of Indonesia number 40 of 2014 concerning Insurance with the addition of a paragraph for the creation of life insurance policies must be made before a public official or notary.